2010
DOI: 10.1107/s0907444910036681
|View full text |Cite
|
Sign up to set email alerts
|

The 2.7 Å resolution structure of the glycopeptide sulfotransferase Teg14

Abstract: The TEG gene cluster was recently isolated from an environmental DNA library and is predicted to encode the biosynthesis of a polysulfated glycopeptide congener. Three closely related sulfotransferases found in the TEG gene cluster (Teg12, Teg13 and Teg14) have been shown to sulfate the teicoplanin aglycone at three unique sites. Crystal structures of the first sulfotransferase from the TEG cluster, Teg12, in complex with the teicoplanin aglycone and its desulfated cosubstrate PAP have recently been reported [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…As stated above, four highly similar GPA sulfotransferases (StaL, Teg12, Teg13, and Teg14) regioselectively modify unique residues on the teicoplanin-class GPA scaffold. Sequence alignment indicates that these proteins differ mainly in three variable regions (V1, V2, and V3) (17,18). Our current StaL-PAP-DSA structure confirms that the DSA substrate, bound in a productive mode within the active site, interacts with all of these three regions, loops α2/α3 (V1), α6/α7 (V2), and α12/α13 (V3) (SI Appendix, Fig.…”
Section: Structure-based Rationalization Of Mutagenesis Data and Subssupporting
confidence: 53%
See 1 more Smart Citation
“…As stated above, four highly similar GPA sulfotransferases (StaL, Teg12, Teg13, and Teg14) regioselectively modify unique residues on the teicoplanin-class GPA scaffold. Sequence alignment indicates that these proteins differ mainly in three variable regions (V1, V2, and V3) (17,18). Our current StaL-PAP-DSA structure confirms that the DSA substrate, bound in a productive mode within the active site, interacts with all of these three regions, loops α2/α3 (V1), α6/α7 (V2), and α12/α13 (V3) (SI Appendix, Fig.…”
Section: Structure-based Rationalization Of Mutagenesis Data and Subssupporting
confidence: 53%
“…The sulfotransferase enzymes within the Teg cluster share ∼60% sequence identity with StaL, and all use the 3′-phosphoadenosine 5′-phosphosulfate (PAPS) cofactor as the source of the sulfate group, converting it to the product 3′-phosphoadenosine 5′-phosphate (PAP) after transfer to the GPA substrate. The crystal structures of Teg12 complexes (17) and Teg14 apo protein (18) have been reported recently. Their structural similarity to StaL, expected given their sequence similarity, implies that each of these orthologs binds the GPA aglycone in a different way, exposing different parts of the GPA aglycone to the enzyme active site.…”
mentioning
confidence: 99%
“…StaL was the first GPA sulfotransferase to have its 3D structure determined by X-ray crystallography, which showed that the protein exists as a dimer and has a dimerization motif unique from the other known sulfotransferases . The subsequent determination of the structures of two additional sulfotransferases, Teg12 and Teg14 with alternate regiospecificity, suggests that these enzymes must have a unique substrate binding pattern in their variable regions, to orient the active site toward different parts of the heptapeptide scaffold. Recent updates from co-crystallization of StaL bound to the substrate (desulfo-A47934) and product of sufate donation (3′-phosphoadenosine 5′-phosphate) have improved our understanding of the reaction .…”
Section: Glycopeptides: a Model Platform To Explore Antibiotic Synthe...mentioning
confidence: 99%